Assessment of Environmental Impact on the Prevalence of Allergic Diseases in the Region (Eurasian Scientific Herald, 2023)
In recent years, more and more data have appeared showing that the pathology of two systems - immune and nervous - can be one of the potential mechanisms mediating the development of a wide range of mental disorders, and, above all, neurodevelopmental disorders (attention deficit and hyperreactivity syndrome, autism spectrum disorders) (ASD), schizophrenia spectrum disorders. Among neurodevelopmental pathologies, ASD is of the greatest concern, due to high heterogeneity and steady growth in the last 20 years, which cannot be explained only by increased awareness and improved clinical diagnostics, which complicates the diagnosis and treatment of this pathology